Microsatellite Markers - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2016)
Microsatellite or so-called simple sequence repeat (SSR) markers have been one of the most reliable molecular markers derived from the DNA molecule, which were widely and successfully used for more than 25 years in the genetic studies of environmental, agricultural, and biomedical sciences. The objective of this Microsatellite Markers book is to rehighlight and provide some updates on previous and recent utilization of microsatellite markers for various applications in agriculture and medicine, which void emerging opinion on "full death" of microsatellites as useful genetic markers. Chapters presented here demonstrate the future benefit of SSRs in many genetic studies as well as disease diagnosis and prognosis.